Blockchain-based traceability system for supply chain: potentials, gaps, applicability and adoption game. Issue 12 (2nd December 2022) - Ni, Shiying; Bai, Xiwen; Liang, Yuchen; Pang, Zhibo; Li, Lefei
ABSTRACT: There are hypes towards blockchain-based traceability systems (BCTS) both from academia and industry. This paper discusses challenges and policy recommendations for BCTS from a viewpoint of industrial application and market competition. First, the potentials of BCTS and the gaps between the ideal and the reality of BCTS are elaborated. Second, we discuss the applicability of BCTS. Third, by a game-theoretic model, we study when supply chains should invest in BCTS. Investment is recommended when investment cost is relatively low compared to the price and market competition is less intense. A prisoner's dilemma arises when investment cost is at a moderate level.